The Eco-philosophical Breakthrough: Zdzisława Piątek’s Concept - Fiut, Ignacy S. (Problemy Ekorozwoju, 2011)
In the opinion of Zdzisława Piątek, the eco-philosophical breakthrough has its genesis in the development of 20th century new axiology indicating, that the value of “sustainability of life” constitutes the highest value for man. On the moral plane, it becomes the source of biocentric and and ecocentric attitudes, lessening human “species chauvinism”. Such attitudes are characterized by the profound axiological conviction that nature as the original environment of human existence possesses internal value, and therefore must constitute the source of ethical concern as a morally vital object. Consequently, man as a source of ethical choices should be responsible for nature’s mode of being, which is strictly related to the quality of his life and dignity, as well as defines the fate of future generations of mankind. According to Zdzisława Piątek, the development of natural and biological sciences constitutes another important cause of eco-philosophical breakthrough. Presently, these sciences provide vast rational knowledge concerning the real relationships between humans, both their biological and cultural essence, and their natural living base. This knowledge provides not only assumptions and arguments for the eco-philosophy, but also broadens the spaces of reflection over the role and place of man within the natural being, and also the future of this natural coexistence. Zdzisława Piątek also believes that the progress of natural and biological sciences must be evolution-oriented on the level of philosophical analysis, and should correspond to the development of social sciences and humanities in order, that the understanding of man as a link of historical process of evolution would be possible, alongside his mind and its symbolic outcomes, creating his culture and generating the forms of social interactions. This knowledge presents the real situation of man within the system of biosphere and renders it possible for him to make critical use of scientific achievements in order to assure a harmonious coexistence of people and nature, as well as the further development of their specific species characteristics, the expression of which is culture. Zdzisława Piątek also criticizes the idealistic and radically anthropocentric attitudes which juxtapose the cultural essence of man with his relationships with the natural determinants of his existence, for instance the concept of “intelligent design”. Such attitudes limit the freedom of scientific research and prevent the rational use of scientific discoveries that could serve the improvement of the quality of human life and actual dignity of man.